A population based study on injuries in rural and urban areas of Aligarh. (1st March 2011) - Zaidi, S H N; Khan, Z; Khalique, N; Amir, A
Abstract : Background: Worldwide injuries and violence are ranked among the leading causes of death and disability. In India, the currently available injury data are hospital derived. In order to understand the burden and outcome associated with injuries, we conducted a community based study in urban and rural area of Aligarh. Methods: Community based cross-sectional study was conducted from August 2006 to July 2007. Data were gathered on 1864 individuals of all ages. The urban sample included 607 individuals while the rural sample included 1257 persons. People having suffered from injury resulted in losing one or more days of normal activity in the last 6 months and all injury-related deaths during the last 1 year were included in the study. Results: The proportion of individuals who sustained injury in rural area was much higher, with an injury incidence of 116 per 1000 persons (95% CI=114.2 to 117.8) compared to urban area with an injury incidence of 88 per 1, 000 persons (95% CI 85.8 to 90.2) of the total population. A significant difference was also found for major disability (>30 disability days) in both areas, with an incidence of 44 per 1000 persons per year (95% CI 42.8 to 45.2) in rural areas and 28 per 1000 persons (95% CI to 26.6 to 29.4) in urban areas. In both areas, the most common cause of injury was Stab/ cut, followed by falls and traffic injury. Conclusion: The urban-rural contrasts in injury mortality and morbidity are due to differences in infrastructure and livelihoods. This has greater implications in setting priorities when planning for intervention strategies.